Collaboration among Local Government Institutions in Achieving Public Information Openness (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2018)
Open Government is one of the main roads for accelerating development and ensuring sustainable development.One of the strategies to encourage open government is by implementing what is the mandate of the Law on public information openness well.For citizens, this law means a guarantee to citizens to obtain public information in order to increase their active role in governance.As for government institutions, the law provides the obligation to government institutions to open access to public information, actively (without preceded by the request), and passively (with the request by the requestor) to the community.However, when citizens try to access the public information, it is not uncommon for the answer to be obtained is